Effect of Salinity on Embryonic Development of the Cuttlefish Sepia pharaonis. Issue 4 (3rd June 2016) - Peng, Rui‐Bing; Wang, Peng‐Shuai; Jiang, Mao‐Wang; Ruan, Peng; Han, Qing‐Xi; Jiang, Xia‐Min
Abstract: The effect of salinity on the embryonic development of Sepia pharaonis eggs was tested experimentally using S. pharaonis embryos at various developmental stages. The hatching rate, incubation period, hatching period, wet weight of hatchling cuttlefish, and yolk utilization efficiency ratio were quantified at salinities of 18, 21, 24, 27, 30, 33, and 36. These variables were significantly affected by salinity. The weight of the eggs first decreased and then increased during embryonic development. The range of suitable salinities for hatching of S. pharaonis eggs was 27–33, and the optimal salinity was 30.